2019
DOI: 10.3390/cancers11060761
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Mitochondrial Ion Channels to Chemo-Resistance in Cancer Cells

Abstract: Mitochondrial ion channels are emerging oncological targets, as modulation of these ion-transporting proteins may impact on mitochondrial membrane potential, efficiency of oxidative phosphorylation and reactive oxygen production. In turn, these factors affect the release of cytochrome c, which is the point of no return during mitochondrial apoptosis. Many of the currently used chemotherapeutics induce programmed cell death causing damage to DNA and subsequent activation of p53-dependent pathways that finally l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 173 publications
3
28
0
Order By: Relevance
“…ROS in turn may activate MPTP or the caspase-independent ROS-triggered parthanatos (poly (ADP-ribose) polymerase-1 dependent cell death). In addition, MPTP can also be triggered by Ca2+overload in the mitochondrial matrix or by IMM depolarization and by several other factors (for example oxidative stress) [ 65 ].…”
Section: Mitochondrial Ion Channels As a Target In Combating Cancementioning
confidence: 99%
“…ROS in turn may activate MPTP or the caspase-independent ROS-triggered parthanatos (poly (ADP-ribose) polymerase-1 dependent cell death). In addition, MPTP can also be triggered by Ca2+overload in the mitochondrial matrix or by IMM depolarization and by several other factors (for example oxidative stress) [ 65 ].…”
Section: Mitochondrial Ion Channels As a Target In Combating Cancementioning
confidence: 99%
“…4b, curve 2), which suggested that RSV may specically induce mPTP opening and NADH release in cancer cells. [62][63][64] This is a very exciting result but the underlying mechanism needs to be deeply investigated.…”
Section: Resveratrol Specically Triggers Mcf-7 Cancer Cells To Releamentioning
confidence: 99%
“…Many recent reviews describe the role of mitochondrial ion channels in cell death, especially in apoptosis and necrosis ( Biasutto et al, 2016 ; Krabbendam et al, 2018 ; Magri et al, 2018 ; Szewczyk et al, 2018 ; Peruzzo and Szabo, 2019 ). In this minireview, we provide an updated overview specifically on the link between the complex regulation of the IMM channels and death induction, with special attention given to the permeability transition pore (PTP) and the mitochondrial calcium uniporter, two master regulators of cell fate.…”
Section: Introductionmentioning
confidence: 99%